If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -3 = 62 Reorder the terms: -3 + 5n = 62 Solving -3 + 5n = 62 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5n = 62 + 3 Combine like terms: -3 + 3 = 0 0 + 5n = 62 + 3 5n = 62 + 3 Combine like terms: 62 + 3 = 65 5n = 65 Divide each side by '5'. n = 13 Simplifying n = 13
| 3x-46=-1x+2 | | 3a+8=2 | | 3.5*10+6= | | 10(x+6)=33 | | -2x=-5y+8 | | 5x-2y=8 | | 3x-2(7)=5x | | 6r+2=3r+11 | | -5.6x=3.5 | | -3x=10 | | 2(x-3)=5 | | -2(4-m)=10 | | 3(k-2)=18 | | 5(6+j)=45 | | 5p-16=54 | | 34=3(f-2)+4 | | 5x+8=3x-3 | | 70=8(c+4)-2 | | 2+3=2y+1-y | | 2x+1=(-15) | | 3x-8+4x+8=180 | | (-4)x+6=(-42) | | (-27)+4n=33 | | 9(y-1)-4y=1 | | (-5)n+9=(-46) | | 9x+2=47 | | 5(m+3)-8=37 | | (-7)n-20=(-48) | | 12n+2=(-46) | | (-5)-15n=10 | | 13-5x=15-17 | | 3(t+10)=t+9 |